Factors related to periodontal disease in a rural population Fatores associados à doença periodontal em uma população rural - Taíze Cassia Nascimento de Macêdo; Maria da Conceição N. Costa; Isaac Suzart Gomes-Filho; Maria Isabel P. Vianna; Carlos Teles Santos (Sociedade Brasileira de Pesquisa Odontológica, 2006)
To estimate the prevalence and related aspects of periodontitis in a rural area of the State of Bahia, Brazil, this cross-sectional study was carried out in the village of Matinha dos Pretos, Feira de Santana County, Bahia, among 172 subjects ranging from 20 to 60 years of age. During household visits, a full-mouth periodontal exam was performed on each subject, who also answered a questionnaire about socio-demographic, economic and health-related issues. The factors assessed were plaque index, bleeding on probing index, probing depth, gingival recession or hyperplasia measurements. Clinical attachment loss was also calculated. The multivariate logistic regression method was used to evaluate the relative contribution of these factors to the periodontitis condition. The prevalence of periodontitis was 24.4%. The following factors were all positively associated with the presence of periodontitis: being male (OR = 1.58; 1.00 - 2.53), being 30 years of age or older (OR = 2.80; 1.00 - 7.39), living in a house where there was more than one person per room (OR = 1.53; 0.96 - 2.45), being a cigarette or pipe smoker or ex-smoker (OR = 1.49; 0.92 - 2.39), having a plaque index of over 65% (OR = 2.97; 2.72 - 7.39) and more than four missing teeth (OR = 1.51; 0.82 - 2.78). The authors concluded that socioeconomic and biological factors, especially poor oral hygiene and older age, are positively associated with periodontitis in the rural population of a small village in the county of Feira de Santana, State of Bahia, Brazil. Para estimar a prevalência e os fatores associados à periodontite em uma área rural do Estado da Bahia foi realizado um estudo transversal com 172 indivíduos, de 20 a 60 anos de idade residentes no povoado de Matinha dos Pretos, Feira de Santana (BA). Durante visitas domiciliares, um exame clínico periodontal completo foi realizado para cada indivíduo, que também respondeu a um questionário a respeito de fatores sociodemográficos, econômicos e relacionados à saúde. Foram avaliados índice de placa, índice de sangramento à sondagem, profundidade de sondagem, medidas de recessão ou hiperplasia e calculada a perda de inserção clínica. Utilizou-se análise de regressão logística multivariada para avaliar a contribuição relativa desses fatores para a periodontite. A prevalência da doença periodontal foi de 24,42%. Ser homem (OR = 1,58; 1,00 - 2,53), ter 30 anos ou mais de idade (OR = 2,80; 1,00 - 7,39), residir em casas com mais de uma pessoa por cômodo (OR = 1,53; 0,96 - 2,45), fumar ou ser ex-fumante de cigarro ou cachimbo (OR = 1,49; 0,92 - 2,39), ter índice de placa maior do que 65% (OR = 2,97; 2,72 - 7,39) e mais de quatro dentes ausentes (OR = 1,51; 0,82 - 2,78) estiveram associados positivamente com a presença de doença. Concluiu-se que fatores socioeconômicos e biológicos, especialmente a higiene bucal inadequada e idade elevada, estão associados positivamente com a presença de periodontite na população rural de um povoado no Estado da Bahia, Brasil.